Integration of Digital Technology in Academics - Mishra, Sunil K.; Shyam Narain, Renuka (International Journal of Humanities and Education Development (IJHED), 2024)
The report aims to identify level of technological integration in academics. Digital literacy enhances learning and knowledge of learners. The benefits of digital literacy are evident in the students’ progress. Active learning is obtained through digital technology as well as literacy enhancement. Considering these benefits, an analysis of technology integration is conducted. The analysis reveals that desired level of technology integration is not achieved in academics. There are several barriers of poor technology integration. Poor technological infrastructure, budget deficit and poor access to technological resources are identified. Lack of time to devote learning of technological competencies is also reported by the analysis. Lack of resources, limited access, insufficient knowledge and skills of teachers and support staffs, lack of support from administrative and teachers, as well as other factors are found responsible for poor technological integration in academics. Institutional barriers are also identified as barriers such as poor leadership or structure of academic institutions. Leader’s inability to understand relevance of technology for learning is a major hindrance. In assessment, teachers do not have sufficient time to implement technology thus they do not use the technological aspects fruitfully. Lack of professional development of the teachers is also a barrier. Many teachers and supportive staff want to maintain the status quo and do not feel that technology integration is required. Such attitudes also prevent technology integration in the academic institutions. Thus, several recommendations are provided by the report such as providing professional development opportunities to the teachers, creating a shared vision, involving stakeholdes, findings cheaper alternatives for digital tools use, seeking grants and funds from government and private organizations, addressing resistance to change by providing training regarding benefits of technology adaption in the classroom etc. the recommendations also include rotating classes and students in groups for collaborative learning, appointing students helpers, allotting more times to the teachers for technological competencies, arranging regular meetings for technology integration, addressing issues of lack of resources, etc. These recommendations can help the academic institutions to integrate technology well in academics